Mitos Tradisi Perayaan Tahun Baru Imlek - Jepriyanti Br Tambunan; Sridevi Hutauruk; Zeco Hamos Sianno Pardede (PANTUN, 2017)
Indonesian has about 300 ethnic groups. Each ethnic groups has an ethnic heritage developed over the centuries that is infuenced by Indian, Arabic, European and Chinese culture, that is Chinese New Year. The celebrations of Chinese Lunar New Year are held by the farmers in China on the first day of the frst month at the beginning of the new year. This celebration is also closely related to the spring festival that begins on the 30th of the 12th month and ends on the first 15th of the month or better known as Cap Go Meh. This Lunar New Year tradition falls in February. Imlek began to be known since the time of the Xia Dynasty. At the celebration of Chinese New Year, many myths are still believed by the Chinese community. Myths are believed to be something that some people believe, commonly used to frighten, warn, or tell them in a sustainable way. This study tries to fnd out the myths of Chinese New Year tradition. The study applies the theory of Bronislaw Malinowski. The result of the study shows the myth of tradition from the Chinese New Year celebrations in Chinese society.Keywords: Chinese New Year, tradition, myth